The National Service Framework for Coronary Heart Disease - Hobbs, R (2002)
Cardiovascular disease is the most important cause of illness in Britain. The focus of the National Service Framework for Coronary Heart Disease (NSF for CHD) is appropriate since the burden of CHD is high in the UK. Interventions for primary and secondary prevention include advice on reducing modifiable risk factors, smoking, maintaining blood pressure < 140/85 mmHg and using statins and dietary advice to lower serum cholesterol. Identification of those at greatest risk will require practice-based registers. Audits will be needed to ensure that the stipulated interventions are offered to those on the disease registers. The biggest implication for primary prevention will be selection of patients at increased risk of CHD. Implementation of the NSF will increase GPs' workload.